PENGEMBANGAN DATABASE SISTEM INFORMASI AKADEMIK SEKOLAH ALAM INDONESIA CIBINONG - Mardiyono, Anggi; Hermawan, Indra; Wirawan, Chandra; Iswara, Ratna Widya; Ramadhan, Muhammad Bintang; Azzahirah, Syifa (Jurnal Abdi Insani, 2025)
Sekolah Alam Indonesia Cibinong faces challenges in managing academic data, which is currently handled manually, leading to inefficiencies and the risk of data loss. In the digital era, the development of a database-based academic information system has become an urgent need to improve efficiency, security, and accessibility of academic data. This activity aims to develop a structured, modern, and database-driven academic information system to support school operations. The methods used include needs analysis through interviews and surveys, system design using an Entity Relationship Diagram (ERD), web-based database implementation, and user training. The development process has included implementation, training, and user evaluation (User Acceptance Testing), with the evaluation results indicating that the system is well-received by key users. These findings demonstrate that the system has been successfully implemented as planned, contributing significantly to improving the efficiency of academic data management. This development is expected to serve as a model for other educational institutions facing similar challenges. Moving forward, feature enhancements and sustainability monitoring are required to ensure optimal benefits of the system.